2013
DOI: 10.1007/s12571-013-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of wild vegetable species in household food security in maize based subsistence cropping systems

Abstract: Wild vegetables (WV) are an important source of food in the maize based subsistence farming sector of rural South Africa. Their main role is as relish as they are used as an accompaniment for staple cereal based diets. They are generally reported to be rich in micronutrients. Although they may be consumed in small quantities, they influence the intake of cereal staples, manage hunger and play a central role in household food security for the poorer rural groups. Mixing several WV species in one meal contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 25 publications
9
91
2
2
Order By: Relevance
“…Those who did not consume forest foods in the two 24 h recalls in the present study did not consume meat and meat products, while bush meat was predominantly consumed by those who consumed forest foods. This is in contrast with the findings reported among rural populations of South Africa which indicated that wild vegetables are consumed only when meat and exotic vegetables cannot be afforded (52) . Nevertheless, the nutrient intakes from forest foods in the present study are higher than those reported in similar studies conducted in DR Congo (12) and Benin (53) .…”
Section: Contribution Of Forest Foods To Nutrient and Energy Intakescontrasting
confidence: 99%
“…Those who did not consume forest foods in the two 24 h recalls in the present study did not consume meat and meat products, while bush meat was predominantly consumed by those who consumed forest foods. This is in contrast with the findings reported among rural populations of South Africa which indicated that wild vegetables are consumed only when meat and exotic vegetables cannot be afforded (52) . Nevertheless, the nutrient intakes from forest foods in the present study are higher than those reported in similar studies conducted in DR Congo (12) and Benin (53) .…”
Section: Contribution Of Forest Foods To Nutrient and Energy Intakescontrasting
confidence: 99%
“…Mavengahama et al (2013) argue that wild vegetables are an important source of food in the maize-based subsistence-farming sector of rural South Africa. Their main role is as an accompaniment to staple, cereal-based diets.…”
Section: Wild Vegetables and Dietary Diversitymentioning
confidence: 99%
“…They may also contribute to greater dietary diversity and be essential components of an otherwise monotonous and nutritionally poor diet (Grivetti and Ogle 2000;FAO 2005;Fentahun and Hager 2009). A number of authors stress the high nutritional (micronutrient) content of WEPs Steyn et al 2001;Odhav et al 2007;Kuhnlein et al 2009;Mavengahama et al 2013). Lastly, WEPs, in some cases, also represent an inextricable link between people and their lands, defining bio-cultural identity (Barucha and Pretty 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have argued that WEPs are important in local food systems and make significant contributions to the food and nutrition security of the poor (Lockett et al 2000;Mahapatra and Panda 2012;Mavengahama et al 2013;Fentahun and Hager 2009;Legwaila et al 2011;Shackleton 2003). However, studies actually quantifying the contributions of WEPs to diets are scattered and use different methodologies, making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation